Solitary polypoid ganglioneuroma in the sigmoid colon: a rare finding during colonoscopy - Bowles, Madison (International Surgery Journal, 2021)
Ganglioneuromas (GN) are rare, benign tumours of the autonomic nervous system which are seldom encountered in the gastrointestinal tract. They may occur as solitary lesions or more commonly as multiple lesions, also known as ganglioneuromatosis. Endoscopically they have no identifiable phenotypic characteristics and therefore diagnosis can only be confirmed through histological analysis. Microscopically they are composed of ganglion cells, nerve fibres and Schwann cells and show S-100 protein immunoreactivity. Clinically, there are no specific symptoms eluding towards the diagnosis of solitary ganglioneuromas of the gastrointestinal tract with most patients remaining asymptomatic. Due to their rarity, no guidelines current exists for solitary colonic GNs, however consensus exists that endoscopic resection is curative with no evidence of recurrence following total excision. This case gives an account of a solitary colonic ganglioneuroma in the sigmoid colon encountered during a screening colonoscopy in a 47-year-old male.